Adaptation strategies of Cunninghamia lanceolata seedlings to light intensity gradients based on morpho-physiological trade-offs - Liu, Qingqing; Huang, Zhijun; Zou, Xianhua; Ma, Xiangqing; Liu, Bo (Frontiers in Plant Science, 2025)
IntroductionCunninghamia lanceolata (Lamb.) Hook is a high-quality, fast-growing plantation-tree species widely distributed in southern China, and a commercial timber species unique to China that plays a vital role in meeting wood demand and maintaining ecological security. Although the morphological and physiological adaptations of C. lanceolata seedlings to light stress have been extensively documented separately, their interplay remains a critical gap in our knowledge and understanding of plant ecophysiology. Particularly, the synergistic mechanisms between phenotypic adaptations and metabolic regulation remain unclear.MethodsThis study employed 1-year-old, clonal, C. lanceolata seedlings as test materials to investigate the coordinated effects of different light intensity gradients (100%, 68%, 27%, 12%, and 5% of full sunlight) on the morphological and physiological responses.Results(1) Under decreasing light intensity, seedling height to diameter ratio and specific leaf area were 30.10% and 64.38% greater than of those recorded under 100% light intensity. The observed changes in growth maximized light capture capacity. Further, root growth, root to shoot ratio, and seedling quality index decreased with decreasing light intensity. (2) Leaf non-structural carbohydrate contents decreased significantly, along with key carbohydrate-metabolizing enzyme activities, and leaf carbon∶nitrogen and carbon∶phosphorus ratios. (3) High light intensities increased cytokinin and abscisic acid contents, whereas the lowest (5%) light intensity tested enhanced the accumulation of gibberellin, but had no significant effect on indoleacetic acid content.DiscussionThese results indicate that C. lanceolata seedlings used a dual adaptation strategy that combined “photoprotection under high light intensity” with “efficient resource utilization under low light intensity” through coordinated morphological and physiological adjustments. Our study provides a scientific basis for managing nursery light conditions and plantation light environment during early development of C. lanceolata seedlings. Specifically, we recommend a 68% light intensity for optimal seedling production.